THE EFFECT OF CORPORATE GOVERNANCE AND QUALITY OF REPORTING ON FIRM VALUES - Dianita Meirini (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2020)
The purpose of this study is to examine the effect of corporate governance and reporting quality on firm value. This study replicates the research conducted by Siagian in 2002. The study examined the effect of the corporate governance index and the quality of financial statement disclosures on firm value. However, this study has differences in the measurements used in Siagian research. In line with the changes in SAK, Bapepam issued a financial statement disclosure checklist whose use is based on Bapepam Rule number VIII.G.7. In this study, researchers aimed to examine the corporate governance index produced through research by The Indonesian Institute for Corporate Governance (IICG) and the quality of reporting using the new checklist standard issued by Bapepam in its influence on company value. This study uses secondary data, from companies registered in the Corporate Governance Perception Index (CGPI) in 20011-2013. The analytical method used is multiple linear regression. The results of this study indicate that the corporate governance index has a significant positive effect on firm value. However, the quality of reporting measured through the disclosure score of financial statements is negatively related and not significant to the value of the company. This shows that investors do not pay much attention to the quality of financial statement disclosures as a basis for determining investment decisions.